2015
DOI: 10.1016/j.bbamcr.2014.09.008
|View full text |Cite|
|
Sign up to set email alerts
|

Ras nanoclusters: Versatile lipid-based signaling platforms

Abstract: Ras proteins assemble into transient nanoclusters on the plasma membrane. Nanoclusters are the sites of Ras effector recruitment and activation and are therefore essential for signal transmission. The dynamics of nanocluster formation and disassembly result in interesting emergent properties including high-fidelity signal transmission. More recently the lipid structure of Ras nanoclusters has been reported and shown to contribute to isoform-specific Ras signaling. In addition specific lipids play critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
329
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(341 citation statements)
references
References 74 publications
11
329
1
Order By: Relevance
“…PtdSer is an anionic phospholipid that is actively concentrated in the inner leaflet of the PM and is required for both the localization of K-Ras to the PM and the assembly of K-Ras4B nanoclusters (18,(34)(35)(36). Ras nanoclusters are essential platforms for generating high-fidelity Ras signal transduction (4,37).…”
Section: Resultsmentioning
confidence: 99%
“…PtdSer is an anionic phospholipid that is actively concentrated in the inner leaflet of the PM and is required for both the localization of K-Ras to the PM and the assembly of K-Ras4B nanoclusters (18,(34)(35)(36). Ras nanoclusters are essential platforms for generating high-fidelity Ras signal transduction (4,37).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that changes in the lipid bilayer thickness cause conformational changes that promote changes in the functional activity of several membrane proteins, including those associated with lipid rafts (25). Among the proteins located in lipid rafts that are involved in signal transduction pathways are the small lipid-anchored Ras GTPases (26,27). There are various Ras isoforms that have been implicated in AmB-induced yeast apoptosis and lethal oxidative damage via the cyclic AMP-protein kinase A (cAMP-PKA) and mitogen-activated protein kinase (MAPK) pathway (28)(29)(30).…”
Section: The Molecular Mechanism Of Signal Transduction Induced By Thmentioning
confidence: 99%
“…Incidentally, H-Ras nanoclusters are enriched in phosphatidylinositols. 57 K-Ras-GTP is similar to H-Ras-GTP in its ability to form nanoclusters on PIP3-rich intact plasma membrane sheets. 57 However, K-Ras-GTP nanoclusters are enriched in phosphatidic acid to a greater extent than either H-Ras-GTP or H-Ras-GDP nanoclusters.…”
Section: Interaction Of Ras Gtpases With Different Membrane Microdomainsmentioning
confidence: 99%
“…57 K-Ras-GTP is similar to H-Ras-GTP in its ability to form nanoclusters on PIP3-rich intact plasma membrane sheets. 57 However, K-Ras-GTP nanoclusters are enriched in phosphatidic acid to a greater extent than either H-Ras-GTP or H-Ras-GDP nanoclusters. 58 Recently, using a phospholipid array binding assay, we found that while GDP-bound full-length wild type K-Ras4B non-specifically interacted with most anionic phospholipids, the GDP-bound oncogenic G12D and G12V mutants preferentially associated with phosphatidylinositol monophosphates and with phosphatidic acid (Banerjee et al, in press).…”
Section: Interaction Of Ras Gtpases With Different Membrane Microdomainsmentioning
confidence: 99%